Analisis Teknik Observasi Dalam Pembelajaran Pendidikan Anak Usia Dini - Suwaryaningrat, Ni Dewi Eka (Jurnal Ilmiah Wahana Pendidikan, 2023)
Observation in early childhood education is an activity carried out by teachers in observing students in order to obtain information about various aspects of development and progress in the learning carried out. Observations carried out continuously are the same as teachers who are developing "Child sense" in early childhood, where children can feel and react to the existing environment, so this research aims to describe observation techniques in learning for early childhood at Gembira Preschool Kindergarten. Tondano. This research was conducted using qualitative research with a phenomenological approach where researchers looked and heard more deeply about learning observation techniques carried out directly at Gembira Preschool Tondano Kindergarten.